GREEKS IN ODESSA (END OF THE 18TH - BEGINNING OF THE 20th CENTURY): HISTORIOGRAPHICAL DIMENSION - Anna Hedo; Olga Sarajeva (Cхід, 2020)
The article has studied and systematized a set of major scientific papers on the ethnic history of the Greeks in Odessa, has identified and argued the stages of development of the historiographical tradition of the problem, has conducted the comparative analysis of directions and priorities of research on the Greeks in Odessa and has traced their evolution in accordance with changes in socio-political context. Historiographical work on the problem has been classified by chronological criteria. It is noted that during the imperial era, research did not go beyond clarifying certain issues of resettlement in the context of the colonization policy of the Russian government. In the research of Soviet historians in the general history of colonization by the Greeks of Odessa, military colonization stands out. At the same time, the socio-economic aspects of the functioning of the Greek community deserved special attention of Soviet historiography. The expansion of the range of research, inclusion of issues of commercial and social activities of Greeks occurs at the present stage of studying the problem and is connected with the intensification of Greek studies in Ukraine. It is proved that the lack of legal autonomy of the Odessa Greek community, the mobility of its representatives did not contribute to the scientific awareness of the Greeks in Odessa (unlike in Nizhyn and Azov) as a separate community with a whole set of distinctive features. Therefore, their history was considered within the context of the history of the foundation and development of the city. Despite the recent appearance of interesting articles on charitable, trade, commercial, cultural and educational activities of the Greek community of Odessa, it is still waiting for an ordered and comprehensive study.